2010
DOI: 10.1007/s12032-010-9613-1
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of vascular endothelial growth factor –2578C/A with cancer risk: evidence from 11263 subjects

Abstract: Published data on the association between vascular endothelial growth factor (VEGF) -2578C/A polymorphism and cancer risk is inconclusive. To derive a more precise estimation of association between VEGF -2578C/A polymorphism and the risk of cancer, we performed a meta-analysis of 5415 cancer cases and 5848 controls from 16 published case-control studies. We used odds ratios (ORs) with 95% confidence intervals (CIs) to assess the strength of the association. Our meta-analysis indicated that VEGF -2578C/A polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…Specifically, we found that women with the VEGFA rs833070 TT genotype and/or increasing copies of the FLT1 ( VEGFR1 ) rs9551471 A allele, had increasing risks of breast cancer in a dose-response manner. These findings are consistent with recent meta-analyses that reported no significant associations between VEGFA -2578 C/A ( rs699947 ), -460C/T ( rs833061 ), and +936 C/T ( rs3025039 ) variants and breast cancer risk (31-35). To date, no genome wide association studies (GWAS) of breast cancer have detected significant associations between VEGF family variants and breast cancer risk.…”
Section: Discussionsupporting
confidence: 92%
“…Specifically, we found that women with the VEGFA rs833070 TT genotype and/or increasing copies of the FLT1 ( VEGFR1 ) rs9551471 A allele, had increasing risks of breast cancer in a dose-response manner. These findings are consistent with recent meta-analyses that reported no significant associations between VEGFA -2578 C/A ( rs699947 ), -460C/T ( rs833061 ), and +936 C/T ( rs3025039 ) variants and breast cancer risk (31-35). To date, no genome wide association studies (GWAS) of breast cancer have detected significant associations between VEGF family variants and breast cancer risk.…”
Section: Discussionsupporting
confidence: 92%
“…However, the reasons for heterogeneity in the analysis of −1082A/G were unclear. It may be due to other factors, including the selection of methods, definition of cases, and sample sizes [19]. We further performed a sensitivity analysis and found the studies by Kung et al [8] and Kolla et al [13] were the main origin of heterogeneity for −1082A/G.…”
Section: Discussionmentioning
confidence: 94%
“…Allele frequency might reflect the natural selection pressures or a balance by other related functional genetic variants and environmental exposures (37,38). Thus, the association between ACE polymorphism and other ethnic groups needed further investigation.…”
Section: Discussionmentioning
confidence: 99%